Anti-aging PVC protective film and preparation method thereof

The silicone polyurethane acrylate obtained by polymerizing polyester polyol and terminal hydroxyl polydimethylsiloxane in PVC protective film, combined with modified magnesium-aluminum hydrotalcite, solves the existing PVC protective film in thermal and UV The aging problem under light has significantly improved its mechanical properties and aging resistance.

CN119410283APending Publication Date: 2025-02-11JIANGYIN JIANGTAI HIGH POLYMER NEW MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411735220.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing PVC protective film is prone to aging under the action of heat and ultraviolet light, resulting in changes in the surface color of the material and a decrease in mechanical properties, which affects its service life.

Method used

Silicone polyurethane acrylate produced by polymerization of polyester polyol and terminal hydroxyl polydimethylsiloxane, combined with ultraviolet-resistant modified magnesium-aluminum hydrotalcite, forms an aging-resistant coating, improving the mechanical properties and resistance of the protective film Aging performance.

Benefits of technology

It significantly improves the mechanical properties and aging resistance of PVC protective film and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005161307310000091
    Figure BDA0005161307310000091
  • Figure BDA0005161307310000101
    Figure BDA0005161307310000101
Patent Text Reader

Abstract

The invention discloses an anti-aging PVC (polyvinyl chloride) protective film which comprises an anti-aging coating, a PVC base material layer and a mounting adhesive layer which are sequentially stacked, and coating liquid of the anti-aging coating comprises the following components in parts by mass: 40-55 parts of organic silicon polyurethane acrylate, 4-6 parts of modified magnesium-aluminum hydrotalcite, 50-60 parts of a reactive diluent and 2-5 parts of a photoinitiator; a modifying agent of the modified magnesium-aluminum hydrotalcite is a silane coupling agent and 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid; and a modifying agent of the modified magnesium-aluminum hydrotalcite is a silane coupling agent and 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid. The organic silicon polyurethane acrylate is prepared from the following raw materials: polyester polyol and hydroxyl-terminated polydimethylsiloxane. Organic silicon polyurethane acrylate is prepared through polymerization of polyester polyol and hydroxyl-terminated polydimethylsiloxane, and ultraviolet-resistant modified magnesium-aluminum hydrotalcite is combined, so that the mechanical property and aging resistance of the protective film are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective films, and in particular to an anti-aging PVC protective film and a preparation method thereof. Background Art

[0002] During use, polymer materials are often affected by environmental factors such as ultraviolet rays, heat, and oxygen, which can cause irreversible aging reactions. Under the action of heat and ultraviolet light, the polymer material PVC protective film will cause the surface color of the material to change, mechanical properties to decrease, physical properties to decrease, etc., thus affecting its service life.

[0003] Therefore, it is necessary to improve the PVC protective film in the prior art. Summary of the invention

[0004] One of the purposes of the present invention is to overcome the defects in the prior art and provide an aging-resistant PVC protective film, which is prepared by polymerizing polyester polyol and terminal hydroxyl polydimethylsiloxane to form an organosilicon polyurethane acrylate, combined with anti-ultraviolet modified magnesium-aluminum hydrotalcite, to improve the mechanical properties and aging resistance of the protective film.

[0005] In order to achieve the above-mentioned process effect, the technical scheme of the present invention is: an aging-resistant PVC protective film, comprising an aging-resistant coating, a PVC substrate layer and an installation adhesive layer stacked in sequence, wherein the coating liquid of the aging-resistant coating comprises 40 to 55 parts of silicone polyurethane acrylate, 4 to 6 parts of modified magnesium-aluminum hydrotalcite, 50 to 60 parts of active diluent, and 2 to 5 parts of photoinitiator by mass fraction;

[0006] The modifier of the modified magnesium-aluminum hydrotalcite is a silane coupling agent and 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid;

[0007] The raw materials of the organosilicon polyurethane acrylate include polyester polyol and terminal hydroxyl polydimethylsiloxane.

[0008] The preferred technical scheme is: the preparation of the modified magnesium-aluminum hydrotalcite is as follows: first, a magnesium-aluminum hydrotalcite matrix is ​​prepared by magnesium salt, aluminum salt and alcohol compound, then an anionic surfactant is added to obtain a colloid, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid is adjusted to a first mixed solution with a neutral pH value by alkali solution, then the colloid is added to the first mixed solution to obtain a preliminary modified magnesium-aluminum hydrotalcite, and finally a silane coupling agent solution is prepared and the preliminary modified magnesium-aluminum hydrotalcite is added to fully react.

[0009] The preferred technical solution is: the alcohol compound is methanol and / or ethanol, and the mass ratio of the magnesium salt, the aluminum salt and the alcohol compound in the magnesium-aluminum hydrotalcite matrix is ​​(1.5-2.5):1:(50-60).

[0010] The preferred technical solution is: the silane coupling agent is γ-methacryloxypropyltrimethoxysilane and / or vinyltrimethoxysilane.

[0011] The preferred technical solution is: the organosilicon polyurethane acrylate is prepared by catalytic polymerization of polyisocyanate and polyol to obtain a polyurethane prepolymer, cross-linking with a chain extender to obtain an urethane polymer, and then end-capping with an ethylenically unsaturated polymer monomer.

[0012] The preferred technical solution is: the polyisocyanate is isophorone diisocyanate, the weight average molecular weight of the terminal hydroxyl polydimethylsiloxane is 1800-2000, and the polyester polyol is polycaprolactone diol; the molar ratio of the terminal hydroxyl polydimethylsiloxane to the polyester polyol is (3-4):1, and the molar ratio of the polyisocyanate to the polyol is (2.2-2.5):1.

[0013] The preferred technical solution is: the chain extender is β-mercaptoethanol and nanocrystalline cellulose, and the molar ratio of the β-mercaptoethanol to the nanocrystalline cellulose is (10-13):1.

[0014] The preferred technical solution is: the ethylenically unsaturated polymerizable monomer is 2-hydroxyethyl acrylate and / or hydroxyethyl methacrylate.

[0015] The preferred technical solution is: the active diluent includes tripropylene glycol divinyl ester and trimethylolpropane triacrylate, and the mass ratio of tripropylene glycol divinyl ester to trimethylolpropane triacrylate is (2-5):1.

[0016] The second object of the present invention is to overcome the defects existing in the prior art and provide a method for preparing an aging-resistant PVC protective film, comprising the following steps:

[0017] S1: prepare coating solution;

[0018] S2: coating the coating liquid on one surface of the PVC substrate layer, and photocuring to obtain a base film with an anti-aging coating;

[0019] S4: preparing a mounting adhesive layer on another surface;

[0020] In S2, the ultraviolet curing energy is 280-300 mW / cm 2 .

[0021] The advantages and beneficial effects of the present invention are:

[0022] The anti-aging PVC protective film is prepared by polymerizing polyester polyol and terminal hydroxyl polydimethylsiloxane to form silicone polyurethane acrylate, and is combined with anti-ultraviolet modified magnesium aluminum hydrotalcite to improve the mechanical properties and anti-aging properties of the protective film. DETAILED DESCRIPTION

[0023] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.

[0024] Modified magnesium aluminum hydrotalcite

[0025] The magnesium salt includes but is not limited to magnesium nitrate, magnesium chloride, magnesium sulfate and hydrates thereof. Further, the magnesium salt is magnesium nitrate hexahydrate.

[0026] Aluminum salts include, but are not limited to, aluminum nitrate, aluminum chloride, aluminum sulfate and hydrates thereof. Further, the aluminum salt is magnesium nitrate hexahydrate.

[0027] The alcohol compound includes, but is not limited to, one or more of methanol, ethanol and propanol. Further, the alcohol compound is methanol and / or ethanol.

[0028] The anionic surfactant is one or more of alkyl sulfonate salts, alkyl sulfonates and alkyl sulfates. Furthermore, the anionic surfactant is sodium dodecylbenzene sulfonate.

[0029] Modification principle: The negatively charged dodecyl sulfonate anion replaces the NO3 between the modified magnesium-aluminum hydrotalcite layers. - Anions enter between the layers, and dodecyl sulfonate anions increase the distance between the main magnesium-aluminum layers, the intercalation space between the main layers becomes larger, and the interaction between the main layers is weakened, which is conducive to the ion exchange between other anions and the dodecyl sulfonate anions between the layers to obtain intercalated hydrotalcite compounds with different structures, effectively preventing the migration of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid small molecules in the aging-resistant coating, resulting in a decrease in anti-ultraviolet performance, which in turn has a negative impact on aging resistance. In addition, the magnesium-aluminum hydrotalcite itself has anti-flame retardancy, which further improves the flame retardancy of the protective film.

[0030] The silane coupling agent is γ-methacryloxypropyltrimethoxysilane and / or vinyltrimethoxysilane. On the one hand, it improves the dispersibility of the modified magnesium-aluminum hydrotalcite in the coating liquid, and on the other hand, the modified double bond polymerizes with the raw materials of the coating liquid to further prevent the migration of small organic molecules in the aging-resistant coating. The silane coupling agent itself contains Si-O bonds, has strong stability and high temperature resistance, and the repolymerization reaction with the raw materials optimizes the crosslinking density of the aging-resistant coating, further improving the aging resistance of the protective film.

[0031] Preparation of modified magnesium-aluminum hydrotalcite: preparation of alkaline solution, mixing NaOH solid and the first methanol solution in a weight ratio of 1:6 at 50°C; mixing magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and the second methanol at room temperature to obtain a first reaction solution; slowly dropping the alkaline solution into the reaction solution at 50°C, stirring at a speed of 3000-4000 r / min, until the pH value reaches 8, stopping the dropping, and continuing the reaction for 24 hours to obtain a second reaction solution containing a magnesium-aluminum hydrotalcite matrix; heating the second reaction solution to 60°C, adding sodium dodecylbenzene sulfonate and stirring the reaction for more than 15 hours. until a colloid is obtained, and the colloid is repeatedly washed with a methanol solvent for later use; 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid is mixed with water and a strong base to obtain a first mixed solution with a neutral pH value, the first mixed solution is heated to 40°C and mixed with the washed colloid, and stirred for reaction for more than 20 hours to obtain a preliminary modified hydrotalcite; the pH value of the prepared silane coupling agent solution is 5.8, the mass ratio of ethanol, water and silane coupling agent is 1:5:0.6, the mixing and hydrolysis time is more than 1.5 hours, the stirring speed is 2500-3000rpm, and the prepared silane coupling agent solution is fully reacted with the preliminary modified hydrotalcite.

[0032] Among them, the second reaction liquid containing the magnesium aluminum hydrotalcite matrix is ​​20 parts, the anionic surfactant is 10 parts, the 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid is 3 parts, and the γ-methacryloxypropyltrimethoxysilane is 6 parts.

[0033] The raw material composition of the obtained magnesium-aluminum hydrotalcite matrix is ​​as follows:

[0034] Sample 1: 2 parts of magnesium nitrate hexahydrate, 1 part of aluminum nitrate nonahydrate and 55 parts of methanol as a second part;

[0035] Sample 2: 1.5 parts of magnesium nitrate hexahydrate, 1 part of aluminum nitrate nonahydrate and 55 parts of the second part of methanol;

[0036] Sample 3: 3 parts of magnesium nitrate hexahydrate, 1 part of aluminum nitrate nonahydrate and a second part of methanol, 55 parts.

[0037] Too much magnesium salt results in too little positive charge on the modified magnesium-aluminum hydrotalcite inorganic layer, affecting the amount of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid embedded between the layers, and further affecting the UV resistance of the protective film; too little magnesium salt is not conducive to the formation of the layer structure of the magnesium-aluminum hydrotalcite matrix.

[0038] Active diluent

[0039] Adjusting the viscosity and rheology of the coating liquid also affects the speed at which oxygen diffuses into the curing system. Tripropylene glycol divinyl ester has a low viscosity, and improving fluidity is conducive to the formation of a film. Although excessive addition of tripropylene glycol divinyl ester improves the mobility of molecules in the curing liquid and increases the number of double bonds in the system, tripropylene glycol divinyl ester with a functionality of 2 has a slow curing speed and an insufficiently dense cross-linked structure, which makes it easier for oxygen to diffuse into the curing liquid system, prolonging the curing time and causing poor film-forming properties. Trimethylolpropane triacrylate has a functionality of 3, is easier to cross-link, and has a denser cross-linked structure, which effectively prevents oxygen from diffusing into the curing liquid and maintains the mechanical properties of the film. Controlling the mass ratio between tripropylene glycol divinyl ester and trimethylolpropane triacrylate can effectively adjust the toughness and hardness of the aging-resistant coating and improve tensile strength and adhesion.

[0040] Photoinitiator

[0041] The photoinitiator is PI 184 and Darocur 1173 in a mass ratio of 1:1. The curing time is optimized to prevent the negative effect of too long curing time on the UV resistance of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid.

[0042] Silicone polyurethane acrylate

[0043] Isophorone diisocyanate (IPDI) has two different types of -NCO groups with different group activities. The reaction conditions can be controlled so that terminal hydroxyl polydimethylsiloxane and polyester polyol react selectively with the -NCO at the aliphatic primary position to form -NCO-terminated polyurethane prepolymers.

[0044] Polycaprolactone diol has good biodegradability and flexibility. Furthermore, its number average molecular weight is 1000-2000, providing good flexibility and mechanical properties. Compared with polyether polyol, it has strong antioxidant properties, further optimizing the anti-aging properties of the protective film.

[0045] The terminal hydroxyl polydimethylsiloxane makes the polyurethane have excellent flexibility and thermal stability. Its weight average molecular weight is 1800-2000. Too small weight average molecular weight has a negative effect on the flexibility and thermal stability of the polyurethane, and too large weight average molecular weight easily leads to a decrease in the transparency of the protective film.

[0046] β-mercaptoethanol is used as a chain extender to improve the repair performance, crosslinking density and high temperature resistance of polyurethane. Nanocrystalline cellulose is used as a chain extender to improve the toughness, crosslinking density and heat resistance of polyurethane. Preparation of nanocrystalline cellulose: Microcrystalline cellulose (MCC) is mixed with a 20% sulfuric acid aqueous solution in a mass ratio of 1:6.2, and then hydrolyzed in a 50°C water bath for 2.5 hours. The hydrolyzate is washed with distilled water to neutrality and then dried at 68°C to a moisture content of less than 1.0%. The acid-hydrolyzed microcrystalline cellulose is then prepared into a 1.2% suspension with distilled water, and the suspension is ultrasonically treated for 600 seconds at a power of 600W using an ultrasonic cell disruptor, and freeze-dried to obtain nanocrystalline cellulose.

[0047] Preparation of silicone polyurethane acrylate: In a reaction vessel under N2 protection, isophorone diisocyanate (IPDI) and a polyol composed of terminal hydroxyl polydimethylsiloxane and polyester diol are dissolved in acetone, 0.5wt% dibutyltin dilaurate (DBTDL) is added dropwise, and the reaction is stirred at 75°C for 4h to obtain a polyurethane prepolymer, and then a chain extender of 3.5% of the total mass of the polyurethane prepolymer is added, 0.5wt% DBTDL and a hydrogen peroxide solution (mass fraction of 35%) and 0.6% sodium iodide in an equal molar amount to β-mercaptoethanol are added dropwise, and the reaction is kept warm for 4h to obtain an urethane polymer, and then 2-hydroxyethyl acrylate is added to cap the reaction at 65°C for 2h to obtain the obtained product. Among them, DBTDL is used to promote the crosslinking of -OH and -NCO phases, and the hydrogen peroxide solution (mass fraction of 35%) and 0.6% sodium iodide promote the formation of disulfide bonds.

[0048] Example 1

[0049] The anti-aging PVC protective film comprises an anti-aging coating layer, a PVC base material layer and a mounting adhesive layer which are stacked in sequence.

[0050] Calculated by mass, the coating liquid of the aging-resistant coating includes 48 parts of silicone polyurethane acrylate, 5 parts of modified magnesium-aluminum hydrotalcite, 56 parts of active diluent, and 3 parts of photoinitiator.

[0051] The photoinitiator is PI 184 and Darocur 1173 in a mass ratio of 1:1. The active diluent is tripropylene glycol divinyl ester and trimethylolpropane triacrylate in a mass ratio of 3.5:1. The modified magnesium aluminum hydrotalcite is prepared by the above-mentioned preparation method of the modified magnesium aluminum hydrotalcite, wherein the magnesium aluminum hydrotalcite matrix is ​​sample 1.

[0052] The organosilicon polyurethane acrylate is prepared by the preparation method of the organosilicon polyurethane acrylate, wherein the molar ratio of polyisocyanate to polyol is 2.3:1, the molar ratio of terminal hydroxyl polydimethylsiloxane to polyester diol is 3.6:1, and the polyester diol is polycaprolactone diol with a number average molecular weight of 1200. The chain extender is β-mercaptoethanol and nanocrystalline cellulose with a molar ratio of 11.5:1.

[0053] The preparation method of the aging-resistant PVC protective film comprises the following steps:

[0054] S1: preparing the above coating solution;

[0055] S2: coating the coating liquid on one surface of the PVC substrate layer and light curing to obtain a base film with an anti-aging coating, wherein the ultraviolet curing energy is 300mW / cm 2 ;

[0056] S4: Prepare a mounting adhesive layer on the other surface.

[0057] Example 2

[0058] Example 2 is based on Example 1, except that, by mass fraction, the coating liquid of the aging-resistant coating includes 40 parts of silicone polyurethane acrylate, 5 parts of modified magnesium-aluminum hydrotalcite, 56 parts of active diluent, and 3 parts of photoinitiator.

[0059] Example 3

[0060] Example 3 is based on Example 1, except that the colloid is first modified by a prepared silane coupling agent solution to obtain a preliminary modified magnesium-aluminum hydrotalcite, and then 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid is adjusted to a first mixed solution with a neutral pH value by an alkali solution, and then the preliminary modified magnesium-aluminum hydrotalcite is added to the first mixed solution for sufficient reaction.

[0061] Example 4

[0062] Example 4 is based on Example 1, except that the magnesium-aluminum hydrotalcite matrix is ​​sample 2.

[0063] Example 5

[0064] Example 5 is based on Example 1, except that the magnesium-aluminum hydrotalcite matrix is ​​sample 3.

[0065] Example 6

[0066] Example 6 is based on Example 1, except that the chain extender is only nanocrystalline cellulose.

[0067] Example 7

[0068] Example 7 is based on Example 1, except that the chain extender is only β-mercaptoethanol.

[0069] Example 8

[0070] Example 8 is based on Example 1, except that the molar ratio of the terminal hydroxyl polydimethylsiloxane to the polyester polyol is 2:1.

[0071] Example 9

[0072] Example 9 is based on Example 1, except that the photoinitiator is only Darocur 1173.

[0073] Comparative Example 1

[0074] Comparative Example 1 is based on Example 1, except that the raw material of the silicone polyurethane acrylate only includes polyester polyol.

[0075] Comparative Example 2

[0076] Comparative Example 2 is based on Example 1, except that the raw material of the silicone polyurethane acrylate only includes terminal hydroxyl polydimethylsiloxane.

[0077] Comparative Example 3

[0078] Comparative Example 3 is based on Example 1, except that the modifier for modifying the magnesium-aluminum hydrotalcite is only 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid.

[0079] Comparative Example 4

[0080] Comparative Example 4 is based on Example 1, except that no modified magnesium-aluminum hydrotalcite is added.

[0081] Performance Test:

[0082] 1. Tensile strength and elongation at break: According to standard: ISO527-3; sample width 25mm, test speed 200mm / min;

[0083] 2. Surface scratch repairability: According to the standard GB / T 2410, the determination method is: the grinding head should meet the requirements of FZ / T 25001 cylindrical fine hair or semi-fine hair abrasive felt, with a density of 0.52±0.052g / cm 2, thickness 10±1mm, diameter 14.5mm±0.5mm, vertical friction test. Frequency 60r / min±6r / min, stroke not less than 100mm, vertical force of grinding head 10N, reciprocating friction 500 strokes, after the friction test, immediately carry out haze measurement (H1), then put the sample into an oven at 55℃±2℃ for 100±5min, take it out and restore it to room temperature and then carry out haze measurement again (H2); calculate the haze change between the two measurements, calculate the haze recovery rate R=(H1-H2) / H2*100%, the test results are expressed as the average haze recovery rate of three samples, and retain to one decimal place.

[0084] 3. Ultraviolet accelerated aging test: Three protective films with a size of 50mm×120mm×1mm were placed in a QUV tester for single-sided (aging-resistant coating facing the light source) anti-ultraviolet aging performance test. They were placed for 7 days, 14 days and 28 days respectively. The ultraviolet aging test standard adopts GB / T 16422.3-2014, and the exposure cycle in the box is 8h / day for drying and 4h / day for condensation; the light source is a fluorescent ultraviolet lamp (UVA-340); the peak wavelength of the ultraviolet lamp is 340nm, and the average radiation intensity of the lamp tube is 0.76W / m 2 The temperature inside the box is controlled at 60±2℃, and the relative humidity inside the box is not controlled; the light source is turned off when watering, the temperature inside the box is controlled at 50±2℃, and the relative humidity inside the box is not controlled; the distance between the protective film and the light source is 30mm.

[0085] The performance tests of the embodiments and comparative examples are as follows:

[0086]

[0087]

[0088] In Example 2, compared with Example 1, as the amount of silicone polyurethane acrylate added is reduced, the mechanical properties and repairability of the protective film are reduced, but the stability of the aging resistance is improved.

[0089] Compared with Example 1, the preliminary modified magnesium-aluminum hydrotalcite is first modified by a silane coupling agent to produce steric hindrance affecting the modification of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, and then the anti-ultraviolet small molecules are dispersed in the aging-resistant coating. In the test, some of them are analyzed to affect the aging resistance of the protective film.

[0090] In Example 5, compared with Example 1, excessive magnesium salt results in too little positive charge on the modified magnesium-aluminum hydrotalcite inorganic layer plate, which affects the amount of 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid embedded between the layers, thereby affecting the anti-aging performance of the protective film.

[0091] Compared with Example 1, in Example 6, the chain extender only improves the cross-linking structure of nanocrystalline cellulose, and the aging resistance is improved, but the repair performance is reduced.

[0092] Compared with Example 1, the reduction in the content of terminal hydroxyl polydimethylsiloxane in Example 8 has a negative impact on the aging resistance of the protective film.

[0093] Compared with Example 1, Example 9 uses a single photoinitiator to prolong the curing time, which has a negative impact on the aging resistance of the protective film.

[0094] Compared with Example 1, although the aging resistance of Comparative Example 2 is improved, the transparency of the protective film is reduced.

[0095] Compared with Example 1, the modifier of the modified magnesium-aluminum hydrotalcite in Comparative Example 3 does not contain a silane coupling agent, resulting in poor dispersibility and a negative impact on both mechanical properties and aging resistance.

[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An anti-aging PVC protective film, comprising an anti-aging coating, a PVC substrate layer and an installation adhesive layer stacked in sequence, characterized in that: The coating liquid of the aging-resistant coating comprises, by mass fraction, 40 to 55 parts of silicone polyurethane acrylate, 4 to 6 parts of modified magnesium-aluminum hydrotalcite, 50 to 60 parts of active diluent, and 2 to 5 parts of photoinitiator; The modifier of the modified magnesium-aluminum hydrotalcite is a silane coupling agent and 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid; The raw materials of the organosilicon polyurethane acrylate include polyester polyol and terminal hydroxyl polydimethylsiloxane.

2. The aging-resistant PVC protective film according to claim 1, characterized in that: The preparation method of the modified magnesium-aluminum hydrotalcite comprises the following steps: firstly, a magnesium-aluminum hydrotalcite matrix is ​​prepared by using magnesium salt, aluminum salt and alcohol compound, then an anionic surfactant is added to obtain a colloid, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid is adjusted to a first mixed solution with a neutral pH value by using an alkali solution, then the colloid is added to the first mixed solution to obtain a preliminary modified magnesium-aluminum hydrotalcite, and finally a silane coupling agent solution is prepared and the preliminary modified magnesium-aluminum hydrotalcite is added to react fully.

3. The aging-resistant PVC protective film according to claim 2, characterized in that: The alcohol compound is methanol and / or ethanol, and the mass ratio of the magnesium salt, the aluminum salt and the alcohol compound in the magnesium-aluminum hydrotalcite matrix is ​​(1.5-2.5):1:(50-60).

4. The aging-resistant PVC protective film according to claim 1 or 2, characterized in that: The silane coupling agent is γ-methacryloxypropyltrimethoxysilane and / or vinyltrimethoxysilane.

5. The aging-resistant PVC protective film according to claim 1, characterized in that: The organosilicon polyurethane acrylate is prepared by catalytic polymerization of polyisocyanate and polyol to obtain a polyurethane prepolymer, cross-linking with a chain extender to obtain an urethane polymer, and then adding an ethylenically unsaturated polymer monomer to cap the end.

6. The anti-aging PVC protective film according to claim 5, characterized in that: The polyisocyanate is isophorone diisocyanate, the weight average molecular weight of the terminal hydroxyl polydimethylsiloxane is 1800-2000, and the polyester polyol is polycaprolactone diol; the molar ratio of the terminal hydroxyl polydimethylsiloxane to the polyester polyol is (3-4):1, and the molar ratio of the polyisocyanate to the polyol is (2.2-2.5):

1.

7. The anti-aging PVC protective film according to claim 5, characterized in that: The chain extender is β-mercaptoethanol and nanocrystalline cellulose, and the molar ratio of the β-mercaptoethanol to the nanocrystalline cellulose is (10-13):

1.

8. The anti-aging PVC protective film according to claim 5, characterized in that: The ethylenically unsaturated polymerizable monomer is 2-hydroxyethyl acrylate and / or hydroxyethyl methacrylate.

9. The anti-aging PVC protective film according to claim 1, characterized in that: The active diluent includes tripropylene glycol divinyl ester and trimethylolpropane triacrylate, and the mass ratio of tripropylene glycol divinyl ester to trimethylolpropane triacrylate is (2-5):

1.

10. A method for preparing an aging-resistant PVC protective film, characterized in that: The following steps are involved: S1: prepare coating solution; S2: coating the coating liquid on one surface of the PVC substrate layer, and photocuring to obtain a base film with an aging-resistant coating; S4: preparing a mounting adhesive layer on another surface; In S2, the UV curing energy is 280-300 mW / cm 2 .

Citation Information

Cited By

  • PVC film surface protective coating and preparation method thereof

    CN121379348A

  • A surface protective coating for PVC films and a method for its production

    CN121379348B